BIBLIOMETRIC STUDIES ON SINGLE JOURNALS: A REVIEW. - Kevin, Wan Utap Anyi; A.N., Zainab; N.B., Anuar (Malaysian Journal of Library and Information Science, 2009)
This paper covers a total of 82 bibliometric studies on single journals (62 studies cover unique titles) published between 1998 and 2008 grouped into the following fields; Arts, Humanities and Social Sciences (12 items); Medical and Health Sciences (19 items); Sciences and Technology (30 items) and Library and Information Sciences (21 items). Under each field the studies are described in accordance to their geographical location in the following order, United Kingdom, United States and Americana, Europe, Asia (India, Africa and Malaysia). For each study, elements described are (a) the journal’s publication characteristics and indexation information; (b) the objectives; (c) the sampling and bibliometric measures used; and (d) the results observed. A list of journal titles studied is appended. The results show that (a)bibliometric studies cover journals in various fields; (b) there are several revisits of some journals which are considered important; (c) Asian and African contributions is high (41.4% of total studies; 43.5% covering unique titles), United States (30.4% of total; 31.0% on unique titles), Europe (18.2% of total and 14.5% on unique titles) and the United Kingdom (10% of total and 11% on unique titles); (d) a high number of bibliometrists are Indians and as such coverage of Indian journals is high (28% of total studies; 30.6% of unique titles); and (e) the quality of the journals and their importance either nationally or internationally are inferred from their indexation status.